Water-based resin composition for coating and coating
By using a specific combination of water-based resin compositions, including incompatible water-dispersed resins and black composites, the difficulty in forming films with high design, low gloss, ultra-low reflectivity and ultra-low L value in the prior art is solved problem, achieving high design and low gloss effects of the film.
Patent Information
- Application Number
- CN202280059781.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-29
- Filing Date
- 2022-09-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-09-16
AI Technical Summary
The prior art is difficult to form films with high design, low gloss, ultra-low reflectivity and ultra-low L values, which cannot meet the demand for improving the design of industrial products in recent years.
By using a specific combination of water -based resin composition, a variety of mixtures that contain the unpredictable water dispersed resin and black complexes with a prescribed particle size range form a low gloss, ultra -low reflectivity and ultra -low L value film Essence
The high design of the membrane has been realized, with low gloss (less than 1.0 %), ultra -low reflectivity (less than 1.5 %), and ultra -low L values (less than 15), which meets the demand for high design and low gloss.
Smart Images

Figure BDA0004724188750000311 
Figure BDA0004724188750000321 
Figure BDA0004724188750000331
Abstract
Description
Technical Field
[0001] The present invention relates to a water-based resin composition for coating and a coating containing the composition. Background Art
[0002] Smartphones, tablet computers, and other electronic devices are coated with a black coating on part or all of their housings (regardless of the outer or inner surface), or on a part of the invisible surface of a glass cover arranged and fixed on the visible side of a touch panel, such as a frame portion, in order to improve design, hide internal wiring, and block light. In recent years, there has been a demand for assembly models such as plastic models, or parts of assembly models in model kits, for a part (e.g., the outer edge of a lens) or all of electronic device components such as lenses mounted on various camera units.
[0003] For example, Patent Document 1 discloses a technique for forming a film by directly applying screen printing made of an insulating material to a housing of a portable electronic device such as a smartphone, or by in-mold molding a film-forming film after screen printing.
[0004] Prior art literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2007-285093 Summary of the invention
[0006] Problem that the invention aims to solve
[0007] However, with the demand for improving the design of industrial products in recent years, there is a need for a black film (eg, a concave-convex film) that can impart higher design to such products.
[0008] The present invention has been made in view of the above circumstances. An object of the present invention is to provide a water-based resin composition for coating that can form a film with high design properties and a coating material thereof.
[0009] Solutions to the problem
[0010] After intensive research, the inventors have discovered that by satisfying the following requirements, a highly designable film can be effectively formed, which, in addition to having low gloss (less than 1.0%), also has an ultra-low reflectivity (less than 1.5%) and an ultra-low L value (less than 15) that are lower than ever before.
[0011] A resin composition having a specific combination is used, which contains, in a specified ratio, that is, a mass ratio range: a resin component containing a mixture of a plurality of mutually incompatible water-dispersible resins; and a black material containing a specific composite having a specified particle size range.
[0012] As an example of a plurality of mixtures contained in the resin component, a mixture containing an acrylic resin emulsion and a polyester resin emulsion in a predetermined mass ratio range is used.
[0013] Based on these findings, the present inventors have completed the invention provided below and solved the above-mentioned problems.
[0014] In the following, (A) is a resin component, (A1) is an acrylic resin emulsion, (A2) is a polyester resin emulsion, (A3) is a water-soluble polymer, (B) is a black material, (B1) is a composite of a black pigment and a resin, and (C) is a diluent solvent.
[0015] According to the present invention,
[0016] A composition can be provided, which is a water-based resin for coating,
[0017] It contains at least (A) and (B),
[0018] (A) a mixture of multiple water-dispersible resins that are incompatible with each other,
[0019] (B) contains 90% by mass or more of (B1) having a particle size of 2 μm or more and 6 μm or less, and the mass ratio of (B) to the resin solid content of (A) is 1:1 and is 1.3 or more and 4.0 or less.
[0020] The above composition may include the following forms.
[0021] (A) contains 90% by mass or more of (A1) and (A2), and the mass ratio of the resin solid content of (A2) to the resin solid content of (A1):1 is preferably 1.8 to 4.4.
[0022] (B1) preferably contains acrylic resin particles containing carbon black.
[0023] (A) may further contain (A3), and in this case, the mass ratio of (A3) to the resin solid content of (A1):1 may be 1.2 to 1.7.
[0024] According to the present invention, a coating can be provided.
[0025] It comprises the above composition and (C),
[0026] The viscosity measured at 25° C. with a B-type viscometer is 1 mPa·s or more and 300 mPa·s or less.
[0027] The above-mentioned coating material may include the following forms.
[0028] Can be used to coat model parts.
[0029] Can be used to coat camera parts.
[0030] Can be used for spraying.
[0031] ·Can be used for coating using a pen-type applicator.
[0032] Can be used for painting with a brush.
[0033] Can be used for dip coating.
[0034] ·Can be used for coating using a dispensing machine.
[0035] According to the present invention, there is provided a pen-type applicator filled with the above-mentioned coating material.
[0036] According to the present invention, there can be provided a film,
[0037] It is formed from the above-mentioned coating material, and,
[0038] The glossiness of the outermost surface of the film-forming surface for incident light at an incident angle of 60° (hereinafter also referred to as "glossiness") is less than 1%, the reflectivity for light of a wavelength of 550 nm (hereinafter also referred to as "reflectivity") is less than 1.5%, and the L value in the CIELAB colorimetric system measured by the SCE method is less than 15.
[0039] The above-mentioned film may include the following aspects.
[0040] If the film needs to have light-shielding properties during transmission, the optical density of the outermost surface of the film-formed surface may be 2.0 or more.
[0041] Effects of the Invention
[0042] According to the present invention, there are provided a water-based resin composition for coating that can form a film with high design properties, and a coating material thereof. DETAILED DESCRIPTION
[0043] The best embodiment of the present invention is described below. However, the present invention is not limited to the following embodiments. Without departing from the gist of the present invention, those skilled in the art can make appropriate changes and improvements to the following embodiments based on common knowledge, and these also fall within the scope of the present invention.
[0044] In the numerical range described in this specification, the upper limit or lower limit of some numerical ranges may be replaced by the numerical values disclosed in the examples.
[0045] In the present specification, the content rate or content of each component in the composition means the total content rate or content of the plurality of substances present in the composition, unless otherwise specified, when there are a plurality of substances corresponding to the components in the composition.
[0046] <Water-based resin composition for coating>
[0047] The water-based resin composition for coatings according to one embodiment of the present invention (hereinafter also referred to as "composition") contains (A) a resin component and (B) a black material. (A) contains a water-dispersible resin mixture, which is a combination of a plurality of water-dispersible resins that are incompatible with each other, and is hereinafter also referred to as "emulsion particles".
[0048] Compared with films formed from conventional water-based resin compositions for coatings, films formed from compositions containing (A) and (B) have lower gloss (less than 1.0%), as well as lower ultra-low reflectivity (less than 1.5%) and ultra-low L values (less than 15). Although the reason is not clear, when (A) contains a water-dispersible resin mixture, an incompatible region is formed in the film after film formation, and as a result, the film after granulation becomes an incompatible film. It is believed that the effects of the incompatible film and (B) incorporated in the film effectively promote the expression of low gloss, ultra-low reflectivity and ultra-low L values.
[0049] -(A)-
[0050] (A) used to form the composition is a fixing material for coating the surface and also a binder for (B). Specifically, it includes a water-dispersible resin mixture that combines multiple (two or more) water-dispersible resins that are incompatible with each other, i.e., emulsion particles. For example, when two water-dispersible resins are combined, one of which is resin A and the other is resin B, resin B is a resin with low compatibility with resin A.
[0051] In this case, the haze value of the film formed by the mixture of resin B and resin A must increase with the increase in the mixing amount. Specifically, a film (thickness 12 μm) formed from a mixture of resin B and resin A mixed at a mass ratio of 1:1 having a haze value of 3.5% or more, preferably 4.5% or more, is defined as a resin incompatible with resin A. The haze value can be measured by the following method.
[0052] Whether or not an "incompatible region" is formed between the combined water-dispersible resins in the formed film can also be confirmed by observing a cross section of the formed film under a microscope to see whether an independent solid phase can be detected.
[0053] By containing a water-dispersible resin mixture, an incompatible region is formed in the film after film formation, and as a result, the film after granulation becomes an incompatible film. In addition, by adding (B) to the incompatible film, the surface of the film becomes low gloss. In addition, it is possible to achieve an ultra-low reflectivity lower than before, and further improve the blackness (L value becomes lower, that is, ultra-low L value). These are the findings of the present inventors.
[0054] In one embodiment, as long as the two water-dispersible resins form an incompatible region in the film after film formation, it is within the scope of the present invention even if a part of one resin A is dissolved in another resin B. When three or more water-dispersible resins are used, each water-dispersible resin may be incompatible with each other, or one water-dispersible resin may be incompatible with a mixed resin formed by two or more other water-dispersible resins that are compatible with each other.
[0055] The combination of water-dispersible resins is selected from two or more of the group consisting of acrylic resin emulsions, polyester resin emulsions, polyurethane resin emulsions, polyvinyl acetate resin emulsions, polyvinyl chloride resin emulsions, polybutadiene resin emulsions, polyolefin resin emulsions, etc. Among them, from the viewpoint of achieving low gloss, ultra-low reflection, ultra-low L value and film strength of the film surface after film formation, a combination containing both acrylic resin emulsions and polyester resin emulsions is preferred.
[0056] In one embodiment, from the viewpoint of forming a film at room temperature and providing the coating surface with desired fixation, the minimum film-forming temperature of the water-dispersible resin mixture is, for example, lower than 40°C, or lower than 0°C.
[0057] Hereinafter, the case where the number of water-dispersible resins combined is two is taken as an example, that is, the combination of the above-mentioned resin A and resin B is taken as an example for explanation, and as an example thereof, the acrylic resin emulsion is abbreviated as (A1) and the polyester resin emulsion is abbreviated as (A2) for explanation. In addition, the combination of (A1) and (A2) is only a preferred example (one embodiment). Therefore, the present invention is not limited to this embodiment.
[0058] (A1)
[0059] The water-dispersible resin mixture contained in (A) contains (A1), so that a film having excellent water resistance and excellent adhesion to the coating surface can be formed. In addition, the formed film has advantages such as film strength and light resistance.
[0060] (A1) constituting a part of (A) contains an acrylic resin and is further contained in the composition of the present invention in an emulsion state. Here, "emulsion state" refers to a state in which the resin contained in the resin emulsion is dispersed in the composition as fine particles. The resin in the emulsion state generally has the property of thickening and coagulating when the aqueous solvent as the continuous phase decreases due to evaporation, penetration, etc., and can promote adhesion to the coating surface.
[0061] Examples of the acrylic resin in (A1) include polymers obtained by polymerizing one or more free radical polymerizable monomers. For example, (A1) can be obtained by polymerizing one or more functional group-containing monomers selected from (meth)acrylic acid, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, adducts of hydroxyethyl acrylate and ε-caprolactone, and monomers selected from (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, and lauryl (meth)acrylate as aqueous emulsions.
[0062] Examples of aqueous emulsification include a method of performing solvent polymerization and then emulsifying in water using forced stirring or an emulsifier, and an emulsion polymerization method of performing copolymerization in water using an emulsifier.
[0063] In one embodiment, (A1) includes an acrylic resin having at least one of a hydroxyl group and a carboxyl group, for example, includes an acrylic resin having a hydroxyl group and a carboxyl group.
[0064] In one embodiment, the acrylic resin in (A1) is crosslinkable resin particles, for example, acrylic resin particles having crosslinkability and having at least one of a hydroxyl group and a carboxyl group.
[0065] In one embodiment, an acrylic resin having a hydroxyl group and a carboxyl group can be obtained by emulsifying and polymerizing a monomer mixture containing an alkyl (meth)acrylate (i), a carboxyl group-containing vinyl unsaturated monomer (ii), and a hydroxyl group-containing vinyl unsaturated monomer (iii). The compounds exemplified below as components of the monomer mixture may be used alone or in combination of two or more. In addition, "meth (acrylic acid)" refers to acrylic acid or methacrylic acid.
[0066] The (meth)acrylic acid alkyl ester (i) is used to constitute the main skeleton of (A1).
[0067] Specific examples of the (meth)acrylic acid alkyl ester (i) include those given as the above-mentioned (meth)acrylic acid alkyl ester.
[0068] The carboxyl group-containing vinyl unsaturated monomer (ii) can be used to improve various stabilities such as storage stability and mechanical stability of the obtained (A1).
[0069] Examples of the carboxyl group-containing vinyl unsaturated monomer include acrylic acid, methacrylic acid, crotonic acid, isocrotonic acid, ethacrylic acid, propyl acrylate, isopropyl acrylate, itaconic acid, maleic anhydride, and fumaric acid.
[0070] The hydroxyl group-containing ethylenically unsaturated monomer (iii) can be used to impart hydrophilicity to (A1) based on the hydroxyl group and can improve the workability when the composition is used as a coating material.
[0071] Examples of the hydroxyl group-containing ethylenically unsaturated monomer (iii) include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, N-methylolacrylamide, allyl alcohol, and ε-caprolactone-modified (meth)acrylic acid monomers.
[0072] Specific examples of the ε-caprolactone-modified acrylic monomer include "Plaxel FA-1", "Plaxel FA-2", "Plaxel FA-3", "Plaxel FA-4", "Plaxel FA-5", "Plaxel FM-1", "Plaxel FM-2", "Plaxel FM-3", "Plaxel FM-4" and "Plaxel FM-5" manufactured by Daicel Chemical Industries, Ltd.
[0073] The monomer mixture may contain at least one monomer selected from the group consisting of styrene monomers, (meth) acrylonitrile and (meth) acrylamide as an arbitrary component. In addition, as styrene monomers, α-methylstyrene and the like can be mentioned in addition to styrene. In addition, as crosslinking monomers, ethylene glycol di(meth)acrylate, divinylbenzene and the like can be mentioned.
[0074] Emulsion polymerization can be carried out by heating the monomer mixture in an aqueous liquid while stirring in the presence of a free radical polymerization initiator and an emulsifier. The reaction temperature is, for example, about 30 to 100° C., and the reaction time is, for example, preferably about 1 to 10 hours. The reaction temperature can be adjusted by adding the monomer mixture or the monomer pre-emulsion all at once or temporarily dropping it into the reaction container into which water and an emulsifier are added.
[0075] As the free radical polymerization initiator, a known initiator commonly used in the emulsion polymerization of acrylic resins can be used. Specifically, as a water-soluble free radical polymerization initiator, for example, a persulfate such as potassium persulfate, sodium persulfate, ammonium persulfate, etc. can be used in the form of an aqueous solution. In addition, a so-called redox initiator can be used in the form of an aqueous solution, which is a combination of an oxidizing agent such as potassium persulfate, sodium persulfate, ammonium persulfate, hydrogen peroxide, etc. and a reducing agent such as sodium bisulfite, sodium thiosulfate, Rongalite, ascorbic acid, etc.
[0076] As the emulsifier, an anionic or nonionic emulsifier selected from micellar compounds having a hydrocarbon group with more than 6 carbon atoms and a hydrophilic part such as a carboxylate, sulfonate or partial sulfate ester in the same molecule can be used. Among them, examples of anionic emulsifiers include: alkali metal salts or ammonium salts of sulfuric acid half esters of alkylphenols or higher alcohols; alkali metal salts or ammonium salts of alkyl or allyl sulfonic acids; alkali metal salts or ammonium salts of sulfuric acid half esters of polyoxyethylene alkylphenyl ether, polyoxyethylene alkyl ether or polyoxyethylene allyl ether, etc. In addition, examples of nonionic emulsifiers include: polyoxyethylene alkylphenyl ether, polyoxyethylene alkyl ether or polyoxyethylene allyl ether, etc. In addition to using these general-purpose anionic and nonionic emulsifiers, various anionic and nonionic reactive emulsifiers containing free radical polymerizable unsaturated double bonds in the molecules, that is, various anionic and nonionic reactive emulsifiers having acrylic, methacrylic, propylene, allyl, allyl ether, maleic acid and other groups can also be appropriately used. These can be used alone or in combination of two or more.
[0077] From the viewpoint of promoting emulsion polymerization and promoting smooth and uniform film formation and improving adhesion to the coated object, when conducting emulsion polymerization, it is often preferred to use a thiol compound, a lower alcohol or the like as an auxiliary agent (chain transfer agent) for adjusting the molecular weight, which can be used appropriately according to the circumstances.
[0078] As emulsion polymerization, any of the following polymerization methods can be used, such as the conventional single-stage continuous monomer uniform dripping method, the multi-stage monomer feeding method, namely the core-shell polymerization method, and the energy feed (Power Feed) polymerization method of continuously changing the fed monomer components during the polymerization process.
[0079] In order to neutralize part or all of the carboxylic acid and maintain the stability of (A1), a basic compound may be added to the obtained (A1). As these basic compounds, ammonia, various amines, alkali metals, etc. can be used appropriately.
[0080] The molecular weight of the acrylic resin in (A1) is not particularly limited, and the weight average molecular weight (Mw) may be, for example, 50,000 to 1,000,000, or 100,000 to 800,000.
[0081] The glass transition temperature (Tg) of the acrylic resin in (A1) may be, for example, from -10°C to 100°C, or from 0°C to 80°C. In addition, the glass transition temperature (Tg) of the acrylic resin may be from 10°C to 80°C. When the glass transition temperature (Tg) is within this range, the acrylic resin can be dispersed in the film and exhibit higher concealment.
[0082] The acid value of the acrylic resin in (A1) may be, for example, 2 mgKOH / g to 20 mgKOH / g, or 5 mgKOH / g to 10 mgKOH / g. When the acid value is within this range, the compatibility with the solvent is improved.
[0083] In addition, the acid value is defined as the mass (mg) of potassium hydroxide (KOH) required to neutralize the acidic components in 1g of the sample (resin solid content), and the same applies hereinafter. Such an acid value can be adjusted according to the type and content of the monomers constituting the resin. The above acid value can be adjusted by, for example, the content of the structural unit derived from the acid group-containing monomer such as (meth) acrylic acid in the acrylic resin.
[0084] The hydroxyl value of the acrylic resin in (A1) may be, for example, 5 mgKOH / g to 20 mgKOH / g, or 10 mgKOH / g to 20 mgKOH / g. When the hydroxyl value is within this range, the advantages of dispersibility and self-crosslinking can be enjoyed.
[0085] The hydroxyl value is defined as the mass (mg) of KOH required to acetylate the hydroxyl groups in 1 g of a sample (resin solid content), and the same shall apply hereinafter.
[0086] The particle size of the acrylic resin in (A1) may be, for example, from 100 nm to 900 nm, or from 200 nm to 500 nm.
[0087] The medium (dispersion medium) in which the acrylic resin is dispersed in (A1) is water or a mixed solvent of water and a water-soluble organic solvent. The water-soluble organic solvent is not particularly limited as long as it is an organic solvent that can be mixed with water, and examples thereof include monohydric alcohols, polyhydric alcohols, lower alkyl ethers of polyhydric alcohols, ketones, ethers, esters, and nitrogen-containing compounds. These can be used alone or in combination of two or more.
[0088] Examples of the monohydric alcohols include methanol, ethanol, n-propanol, n-butanol, isobutanol, n-pentanol, n-hexanol, n-heptanol, n-octanol, n-nonanol, n-decanol, isomers thereof, cyclopentanol, cyclohexanol, etc. Alcohols having an alkyl group with 1 to 6 carbon atoms are preferably used.
[0089] Examples of the polyol include ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,2-pentanediol, 1,5-pentanediol, neopentyl glycol, 1,2-hexanediol, 1,6-hexanediol, 1,2-cyclohexanediol, heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, glycerol, pentaerythritol, diethylene glycol, dipropylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, polypropylene glycol, and thiodiglycol.
[0090] Examples of the lower alkyl ethers of polyhydric alcohols include ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, ethylene glycol monoethyl ether, ethylene glycol diethyl ether, ethylene glycol monopropyl ether, ethylene glycol isopropyl ether, ethylene glycol monobutyl ether, ethylene glycol isobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol n-propyl ether, propylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, dipropylene glycol mono-n-propyl ether, and dipropylene glycol mono-n-butyl ether.
[0091] The content of the water-soluble organic solvent is preferably as little as possible, and may not be added. When added, the content is preferably 0 to 10.0% by mass, more preferably 0 to 5.0% by mass, relative to 100% by mass of the mixed solvent. If it exceeds 10.0% by mass, poor drying or reduced anti-blocking properties may occur.
[0092] The resin solid content concentration (also referred to simply as "solid content") of (A1) may be, for example, 10% by mass or more, preferably 15% by mass or more, more preferably 25% by mass or more, and preferably 50% by mass or less, more preferably 35% by mass or less.
[0093] The pH value of (A1) can be, for example, 4 to 8, or 4 to 7. When the pH value is within this range, the adhesion between the formed film and the coated object can be further improved.
[0094] As (A1), commercially available products can be used, for example, EM57DOC manufactured by Daicel Finechem; Mowinyl 7471, Mowinyl 7540, Mowinyl DM774, Mowinyl 6520 manufactured by Nippon Synthetic Chemical Industry Co., Ltd.; NeoCryl A-639, NeoCryl A-1127 manufactured by Kusumoto Chemicals Co., Ltd.; Vinyblan 278, Vinyblan 690 manufactured by Nissin Chemical Industry Co., Ltd., etc.
[0095] These may be used alone or in combination of two or more.
[0096] (A2)
[0097] When the water-dispersible resin mixture contained in (A) contains (A2), the film formed can be provided with effects such as improvement in film strength.
[0098] (A2) constituting a part of (A) contains a polyester-based resin and is further contained in the composition of the present invention in an emulsion state, which is the same as (A1).
[0099] Examples of the polyester resin in (A2) include condensates of polybasic acids and polyols. Examples of polybasic acids include phthalic anhydride, isophthalic acid, terephthalic acid, adipic acid, and succinic anhydride. 。 Examples of the polyol include ethylene glycol, propylene glycol, 1,3-butanediol, 1,6-hexanediol, polyethylene glycol, and polypropylene glycol.
[0100] In one embodiment, the polyester resin in (A2) preferably has a carboxyl group and / or a sulfonic acid group. Since the polyester resin contains these hydrophilic groups, it has good dispersibility in water, and as a result, the coating containing the composition can form a more uniform film and can further improve the adhesion between the film and the coated object.
[0101] The molecular weight of the polyester resin in (A2) is not particularly limited, and the number average molecular weight (Mn) may be, for example, 6,000 to 20,000, or 8,500 to 20,000.
[0102] The glass transition temperature (Tg) of the polyester resin in (A2) may be, for example, 40° C. to 80° C., or 55° C. to 75° C. When the glass transition temperature (Tg) is within this range, a film having excellent water resistance and excellent adhesion to a coated object can be formed.
[0103] The acid value of the polyester resin in (A2) may be, for example, 1 mgKOH / g to 10 mgKOH / g, or 1 mgKOH / g to 8 mgKOH / g. When the acid value is within this range, the advantage of improved compatibility with solvents can be enjoyed.
[0104] The hydroxyl value of the polyester resin in (A2) may be, for example, 1 mgKOH / g to 20 mgKOH / g, or 1 mgKOH / g to 10 mgKOH / g. When the hydroxyl value is within this range, the advantages of dispersibility and self-crosslinking can be enjoyed.
[0105] The particle size of the polyester resin in (A2) can be, for example, from 10 nm to 300 nm, or from 50 nm to 150 nm.
[0106] As the dispersion medium of the polyester resin in (A2), water or a mixed solvent of water and an organic solvent can be used, similarly to the dispersion medium in (A1).
[0107] The solid content of (A2) may be, for example, 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, and preferably 90% by mass or less, more preferably 80% by mass or less.
[0108] As (A2), commercially available products can be used, for example, KA-5071S, KZT-8803, KT-8701, KZT-9204 manufactured by Unitika Co., Ltd.; VYLONAL MD1200, MD1245, MD1480, MD1930, MD2000, MD1500 manufactured by Toyobo Co., Ltd.; high-tech PE series such as PES-H001 manufactured by Toho Chemical Co., Ltd.; newtrack2010 manufactured by Kao Corporation; SUPERFLEX 210 manufactured by Daiichi Kogyo Seiyaku Co., Ltd.; Pluscoat Z730, Z760, Z592, Z687, Z690 manufactured by Huyo Chemical Co., Ltd., etc.
[0109] These can be used alone or in combination of two or more.
[0110] In one embodiment, the mass ratio of the resin solid content of (A2) in (A) is preferably 1.8 or more, more preferably 2.0 or more, and preferably 4.4 or less, more preferably 3.0 or less, relative to the resin solid content of (A1):1. By adding (A2) within this resin solid content mass ratio range, stable film strength can be obtained, that is, the film will not fall off from the coating surface or have poor adhesion to the coating surface.
[0111] The total content of (A1) and (A2) in (A), i.e., the total amount, is preferably 90% by mass or more, more preferably 95% by mass or more. The upper limit is not particularly limited, but is 100% by mass. That is, in one embodiment, 100% by mass of (A) preferably contains 90% by mass or more of (A1) and (A2).
[0112] When (A) contains other resin emulsions together with (A1) and (A2), the mass ratio of the resin solid content of the other resin emulsion in (A) is, for example, 0.4 or less relative to the total amount of (A1) and (A2):1.
[0113] In addition, the molecular weight (Mw, Mn), glass transition temperature (Tg), acid value, hydroxyl value, particle size, and resin solid content concentration (solid content) of each water-dispersible resin (acrylic resin, polyester resin, and other resins) can be measured by any method known to those skilled in the art.
[0114] For example, the molecular weight (Mw, Mn) of each water-dispersible resin is measured by gel permeation chromatography (GPC). GPC uses HLC-8020GPC manufactured by Tosoh Corporation, 3 TSKgels and SuperMultipore HZ-H manufactured by Tosoh Corporation, 4.6 mm ID×15 cm as chromatographic columns, THF (tetrahydrofuran) is used as an eluent, detection is performed in a solvent THF, and polystyrene is used as a standard substance for conversion to obtain the molecular weight.
[0115] The glass transition temperature (Tg) is measured by the DSC method using a differential scanning calorimeter. More specifically, the glass transition temperature can be measured by a differential scanning calorimeter (DSC), such as a differential scanning calorimeter "DSC-50" manufactured by Shimadzu Corporation. In addition, when multiple glass transition temperatures are observed, the main transition temperature with a larger amount of endothermic heat can be used.
[0116] The acid value and the hydroxyl value are measured according to the method specified in the JIS standard (JIS K0070, 1992), that is, the potentiometric titration method.
[0117] The particle size is the average particle size of primary particles, and is measured (determined) using, for example, a particle size distribution measuring apparatus FPAR-1000 manufactured by Otsuka Electronics Co., Ltd. using a dynamic light scattering method, or by image analysis using, for example, a transmission electron microscope (TEM) or a scanning electron microscope (SEM).
[0118] The solid content of the emulsion was calculated from the residue after drying at 150°C for 2 hours.
[0119] (A3)
[0120] (A) may contain (A3) a water-soluble polymer together with the water-dispersible resin mixture. By containing (A3) in (A), it is expected that the adhesion of the formed film to the coating surface will be improved.
[0121] The water-soluble polymer is not particularly limited as long as it is water-soluble, and examples thereof include polycarboxylic acid polymers, polyvinyl alcohol polymers, cellulose and its derivatives, gelatin, polymers having a structural unit derived from N-vinyl cyclic lactam, etc. These may be used alone or in combination of two or more.
[0122] When (A) contains (A3), polyvinyl alcohol (PVA) is preferably used from the viewpoint of the stability of the composition. Polyvinyl alcohol is a polymer compound obtained by saponifying polyvinyl acetate with an alkali, an acid, ammonia water, etc., and preferably is a partially saponified type having a saponification degree of about 78.5 to 89.0 mol% with good stability of the composition over time. This is so-called polyvinyl alcohol (PVA) with a low or medium saponification degree.
[0123] In addition, the average degree of polymerization is preferably about 300 to 2,300, more preferably about 1,500 to 1,900.
[0124] As (A3), commercially available products can be used. For example, GOHSENOL GH23 (polymerization degree of about 2300, saponification degree of 86.5 to 89.0 mol%), GOHSENOL GH20 (polymerization degree of about 2000, saponification degree of 86.5 to 89.0 mol%), GOHSENOL GH17 (polymerization degree of about 1700, saponification degree of 86.5 to 89.0 mol%), GOHSENOL GM14 (polymerization degree of about 1400, saponification degree of 86.5 to 89.0 mol%), GOHSENOL GL-03 (polymerization degree of about 300, saponification degree of 86.5 to 89.0 mol%), manufactured by Nippon Synthetic Chemical Industry Co., Ltd. GOHSENOL GL-05 (degree of polymerization of about 500, degree of saponification of 86.5 to 89.0 mol%), GOHSENOL KH20 (degree of polymerization of about 2000, degree of saponification of 78.5 to 81.5 mol%), GOHSENOL KH17 (degree of polymerization of about 1700, degree of saponification of 78.5 to 81.5 mol%), GOHSENOL KL-03 (degree of polymerization of about 300, degree of saponification of 78.5 to 82.0 mol%), GOHSENOL KL-05 (degree of polymerization of about 500, degree of saponification of 78.5 to 82.0 mol%); Kuraray Poval PVA-203 (degree of polymerization of about 300, degree of saponification of 86.5 to 89.5 mol%), Kuraray Poval PVA-204 (degree of polymerization of about 400, degree of saponification of 86.5 to 89.5 mol%), Kuraray Poval PVA-205 (degree of polymerization of about 500, saponification degree of 86.5 to 89.5 mol%), PVA-210 (degree of polymerization of about 1000, saponification degree of 88 mol%), PVA-217 (degree of polymerization of about 1700, saponification degree of 88.0 mol%), PVA-220 (degree of polymerization of about 2000, saponification degree of 88.0 mol%), PVA-217EE (degree of polymerization of about 1700, saponification degree of 88.0 mol%), PVA-217 PVA-403 (degree of polymerization of about 300, degree of saponification of 80.0 mol%), PVA-405 (degree of polymerization of about 500, degree of saponification of 83.0 mol%), PVA-420 (degree of polymerization of about 2000, degree of saponification of 81.0 mol%); Denka Poval B-03 (degree of polymerization of about 300, degree of saponification of 87 to 89 mol%) and Denka Poval B-05 (degree of polymerization of about 500, degree of saponification of 87 to 89 mol%) manufactured by Denki Kagaku Kogyo Co., Ltd.; Unitika Poval UP050G (degree of polymerization of about 500, degree of saponification of about 87 to 89 mol%) manufactured by Unitika Co., Ltd.
[0125] These can be used alone or in combination of two or more.
[0126] When (A) contains (A3), the mass ratio of (A3) in (A) is preferably 1.2 or more, more preferably 1.35 or more, preferably 1.7 or less, more preferably 1.55 or less, relative to the resin solid content of (A1):1. By adding (A3) within this resin solid content mass ratio range, the adhesion of the formed film to the coating surface can be easily improved.
[0127] The content, i.e., the total amount, of the resin solid content in (A) is not particularly limited, but in consideration of the mixing balance with other components, it is preferably 10% by mass or more, more preferably 20% by mass or more, further preferably 25% by mass or more, and preferably 50% by mass or less, more preferably 40% by mass or less, further preferably 35% by mass or less, relative to 100% by mass of the total solid content of the composition.
[0128] -(B)-
[0129] (B) used to form the composition includes (B1) a composite of a black pigment and a resin.
[0130] The resin forming the composite with the black pigment is a water-insoluble resin. Examples of such resins include epoxy resins, acrylic resins, polyurethane resins, styrene resins, vinyl resins, phenolic resins, urea resins, amide resins, melamine resins, and benzoguanamine resins. Among them, acrylic resins or polyurethane resins are preferred from the viewpoint of dispersibility, and acrylic resins are more preferred.
[0131] These may be used alone or in combination of two or more.
[0132] In addition, by adding the resin name before the name beads, the name of the resin particles can be partially omitted. For example, resin particles made of acrylic resin can also be called acrylic beads.
[0133] The black pigment that forms the composite with the resin is not particularly limited, but preferably carbon black, which has a great blackening effect on the composite and is reasonably priced, is used, hereinafter also referred to as "CB". By using CB, the formed film will be colored, further improving the anti-reflection effect, and obtaining a good antistatic effect.
[0134] Examples of composite forms of black pigment and resin include: (1) a form in which black pigment is coated with resin (including a form in which black pigment is contained in resin particles); (2) a form in which the resin is combined with the surface or interior of the black pigment; (3) any one of the forms in which the resin is attached to the surface or interior of the black pigment, or a composite form of these.
[0135] As a method of coating the surface of the black pigment with a resin, for example, a microcapsule method can be cited, more specifically, an interfacial polymerization method, an in-situ polymerization method, a liquid solidification coating method (aperture method), an aqueous solution phase separation method, and a liquid drying method. In addition, in addition to the microcapsule method, there is also a method of combining or attaching a resin to a dispersed black pigment. For example, there is a method of using a pigment as a core and covering its surface with a large amount of colloidal resin particles. When a colorant in which a black pigment core is covered with colloidal resin particles is used, it is preferred that the size of the surrounding resin particles is sufficiently small relative to the pigment core. Moreover, it is preferred that the colloidal resin particles cover the pigment core almost without gaps. However, this does not exclude the situation where the pigment core is directly exposed to the outside.
[0136] (B1) may be a resin having the same size as the pigment particles bonded to the pigment. The black pigment or black dye may be kneaded into other thermoplastic resins or thermosetting resins and the mixture may be crushed to form a composite with the resin.
[0137] In one embodiment, from the viewpoint of improving dispersibility, the composite form is preferably form (1), that is, a form in which the black pigment is coated with resin particles. Since the resin particles coated with the black pigment encapsulate the pigment in the resin particles with a larger diameter, it is less likely to form agglomerates in the composition compared to directly adding a pigment with a smaller diameter to the composition, which helps to improve dispersibility.
[0138] The content of the pigment in (B1), particularly CB, is preferably 1% by mass or more, more preferably 5% by mass or more, further preferably 10% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, further preferably 30% by mass or less.
[0139] The particle size of (B1) is preferably 2 μm or more, more preferably 3 μm or more, preferably 8 μm or less, more preferably 6 μm or less, and further preferably 4 μm or less. If the particle size is too small, the aggregates in the composition increase, and there is a tendency for dispersion to become difficult. If the particle size is too large, there is a tendency for the tinting power to decrease.
[0140] The particle size of (B1) refers to a particle size (D50) value when the integral value expressed as the integral of the particle size distribution, that is, the cumulative percentage, is 50%.
[0141] The shape of (B1) is not particularly limited, but from the viewpoint of matting properties, it is preferably a perfect sphere. In addition, in order to achieve further low gloss, low reflection, and low L value on the film-forming surface, it is preferred to use particles with a narrow particle size distribution, such as particles with a coefficient of variation (CV) value of 15 or less, products of Sharp Corporation. The CV value is a numerical value representing the dispersion degree of the particle size distribution relative to the average particle size, i.e., the arithmetic mean particle size, i.e., the particle size dispersion. By using such particles, they can be uniformly contained in the film, and fine concave-convex shapes are formed on the film surface, making it easy to achieve further low gloss, low reflection, and low L value on the film surface.
[0142] In addition, in order to further reduce the glossiness of the film-forming surface, amorphous particles can be used as (B1). By using amorphous particles as (B1), when forming a film, light is repeatedly refracted on the surface and inside of (B1), thereby further reducing the glossiness of the film surface.
[0143] As (B1), commercial products can be used. As products containing polyurethane beads, for example, Art Pearl C800 black manufactured by Negami Industries Co., Ltd., with a particle size of 6.5 μm and a CB content of 7.5%, etc. can be cited. As products containing acrylic beads, i.e., acrylic copolymer beads, for example, Art Pearl GR-004BK manufactured by Negami Industries Co., Ltd., with a particle size of 3.8 μm and a CB content of 37%, and RUBCOULEUR 224 (SMD) black manufactured by Dainichi Seika Industries Co., Ltd., with an average particle size of 2 to 3 μm and a CB content of 18%, etc. can be cited.
[0144] The content of (B1) in (B) is preferably 90% by mass or more, more preferably 95% by mass or more. The upper limit is not particularly limited, but is 100% by mass. That is, in one embodiment, in 100% by mass of (B), (B1) preferably contains 90% by mass or more.
[0145] In one embodiment, the mass ratio of (B) relative to the resin solid content (A): 1 is preferably 1.3 or more, more preferably 1.9 or more, preferably 4.0 or less, more preferably 3.0 or less. By adding (B) within this mass ratio range, low gloss, low reflection, and low L value can be achieved while maintaining the strength of the coating film.
[0146] The content, i.e., the total amount, of (B) relative to the total solid content of the composition (100 mass %) is, for example, 60 mass % or more, preferably 65 mass % or more, more preferably 75 mass % or more, for example, 90 mass % or less, preferably 85 mass % or less, more preferably 80 mass % or less. If the total amount of (B) is less than 60 mass %, problems such as increased gloss and insufficient optical density may occur, and if it exceeds 90 mass %, relatively less (A) is present in the formed film, which may cause the film to fall off from the coated object.
[0147] -Optional ingredients-
[0148] In addition to the above-mentioned components (A) and (B), the composition may also contain any other components as long as they do not hinder the effect of the present invention. However, in the solid content of the composition of 100% by mass, the total mass of the above-mentioned components (A) and (B) is preferably 50% by mass or more. This mass ratio varies depending on the physical properties required for the composition, and is more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more.
[0149] This composition is an aqueous composition in which the above-mentioned emulsions (A1, A2) are dispersed in a dispersion medium.
[0150] The composition of one embodiment of the present invention can be prepared (manufactured) by mixing and stirring (A1), (A2), (B) and any optional components added as needed. The order of mixing the components is not particularly limited as long as the components are mixed uniformly.
[0151] <Water-based paint>
[0152] The water-based coating according to one embodiment of the present invention, which will also be referred to as "coating" hereinafter, is used to form a film made of the above composition on a coating surface, and comprises the above composition and (C) a dilution solvent.
[0153] The content of the above composition in the coating is preferably 90% by mass or more, more preferably 95% by mass or more, relative to 100% by mass of the total solid content of the coating. The upper limit is not particularly limited, but is 100% by mass.
[0154] -(C)-
[0155] (C) used to form the coating is added to adjust the viscosity of the coating. By using (C), the uniformity of the coating is improved. In addition, the viscosity of the coating can be appropriately adjusted, and when forming a film on the coating surface, the operability of the coating and the uniformity of the coating thickness can be improved, which can greatly help improve the design of the final product.
[0156] (C) There is no particular limitation as long as it is a solvent capable of adjusting the viscosity of the coating. Water or a mixture of water and an organic solvent which is the same as the dispersion medium of the emulsion particles can be used. In order to adjust the solid content concentration of the coating, the mixing amount can be appropriately adjusted.
[0157] The viscosity of the coating has an appropriate range that varies depending on the coating method, so it cannot be generalized, but the viscosity at 25°C measured by a B-type viscometer is approximately 1 mPa·s to 300 mPa·s. For example, when the coating method is spraying, it is preferably about 1 mPa·s to 50 mPa·s. When the coating method is dipping, it is preferably about 100 mPa·s to 300 mPa·s. When the coating method is dispensing, it is preferably about 100 mPa·s to 250 mPa·s. In addition, when a pen-type applicator is loaded with coating and used, it is preferably about 80 mPa·s to 230 mPa·s.
[0158] In the case of the spray coating method, if the viscosity of the paint is too low, a film of a thickness that can express the specified performance may not be formed. If the viscosity of the paint is too high, the liquid may not be sprayed out from the nozzle, or even if it is sprayed, it may not be atomized. In the case of the dip coating method, if the viscosity of the paint is too low, severe dripping may occur and unevenness may occur, and a clean film may not be formed. If the viscosity of the paint is too high, when the coated object is lifted from the paint, the paint may be difficult to drain, burrs may occur, or the surface shape of the coating film may become smooth and glossy. In the case of the dispense coating method, if the viscosity of the paint is too low, splashing or dripping may occur, resulting in coating of areas that do not need to be coated. If the viscosity of the paint is too high, the liquid may not be sprayed out from the nozzle, and even if it is sprayed, the surface shape may become smooth and glossy. When the paint is loaded into a pen-type applicator and used, if the viscosity of the paint is too low, the film thickness is too thin, the optical density is insufficient, and it is easy to blur and cannot draw clean lines. If the viscosity of the paint is too high, the pen tip does not discharge liquid, streaks appear, and clean lines cannot be drawn.
[0159] The viscosity of the coating varies depending on the components contained in the composition of the coating, that is, the types and molecular weights of (A) and (B) constituting the composition, etc. In addition, when an arbitrary component is mixed in addition to the above-mentioned (A) and (B), it also varies depending on the type and molecular weight of the arbitrary component, but can be easily adjusted by appropriately determining the amount of (C) in the coating.
[0160] -Other additives-
[0161] In addition to the above-mentioned components, i.e., the composition and (C), the coating may further contain one or more other additives as long as they do not hinder the effects of the present invention. Examples of other additives include: leveling agents, thickeners, pH adjusters, lubricants, dispersants, defoamers, curing agents, and reaction catalysts.
[0162] When other additives are mixed, the mixing amount of the other additives is preferably 0 to 100 parts by mass, more preferably 0 to 30 parts by mass, relative to 100 parts by mass of the solid content of the resin in the coating material.
[0163] The coating material according to one embodiment can be used for coating parts of an assembly model.
[0164] The coating material according to one embodiment can be used for coating camera parts.
[0165] The coating material according to one embodiment can be used for spray coating.
[0166] The coating material according to one embodiment can be applied using a pen-type applicator, a brush, a dip coating method, or a dispense coating method.
[0167] The coating material according to one embodiment can be used by being contained in a pen-type applicator.
[0168] <Coating method, coated object>
[0169] The film according to one embodiment of the present invention is formed by applying the above-mentioned coating material to a coating object to form a coating film, and then drying the coating film.
[0170] The coating method of the above-mentioned coating can be a spraying method, for example, air spraying method, airless spraying method, electrostatic spraying method, etc. By using the spraying method, even if there are protrusions or staggered layers on the surface of the coated object, a film with uniform thickness and specific properties can be formed on the entire surface.
[0171] The coating conditions using the spraying method are preferably: the diameter of the spray gun orifice is about 0.2 to 1.2 mm, the amount of liquid sprayed is about 0.2 to 10 (g / min), the shortest distance between the spray gun and the surface of the coated object is about 30 to 500 mm, the coating speed is about 30 to 300 (mm / sec), the overlap spacing is about 1.5 to 10 mm, and the pressure of the atomizing air is about 0.03 to 0.2 MPa. In terms of the number of spray guns, one spray gun can be used. In addition, from the perspective of improving the coating efficiency, a plurality of spray guns can be configured according to the size of the coated object.
[0172] After the coating is applied to the surface of the object, the solvent is removed by drying to form a film. If necessary, the coating film can be cured by irradiating the coating film with UV light or EB light or by heating the coating film.
[0173] The coating may be applied by, for example, a method using a pen-type applicator such as a marker pen, a brush coating method using a brush, a dip coating method by immersion, or a dispensing coating method, in addition to the spray coating method.
[0174] In one embodiment, the structure of the pen-type applicator is not limited, and examples thereof include a structure including a pen tip, a paint filling mechanism, a pen tip retracting mechanism, a paint supply mechanism, and the like.
[0175] The pen tip of the applicator can be a ballpoint pen tip whose ball is rotatably held in a ball chamber of the pen tip body, i.e., a ball holding chamber. In addition, other refills such as fiber nibs, felt nibs, and plastic nibs, as well as metal fountain pen nibs, can also be listed.
[0176] The paint filling mechanism of the coater may be a structure that directly fills the paint, or may have a paint container or a paint storage body that can be filled with the paint.
[0177] When the paint filling mechanism is a structure for directly filling the above-mentioned paint, it is preferred that a stirring body such as a stirring ball for stirring the paint is built into the paint storage body to promote the redispersion of (B). The shape of the stirring body may be a spherical body, a rod-shaped body, etc. The material of the stirring body is not particularly limited, and specifically, metal, ceramic, resin, glass, etc. may be mentioned.
[0178] When the paint filling mechanism includes a paint storage body, the paint storage body is preferably composed of a fiber bundle made of twisted fibers.
[0179] The pen tip retractable mechanism of the applicator is not particularly limited, and examples thereof include a cap type having a cap covering the pen tip, a knocking type, a rotary type, a sliding type, etc. Alternatively, a retractable type that can accommodate the pen tip in a barrel may be used.
[0180] There is no particular restriction on the paint supply mechanism of the coater, and examples thereof include: a mechanism having a paint guide core composed of a fiber bundle or the like as a paint flow adjustment component, and supplying the above-mentioned paint to the pen tip; a mechanism having a comb-groove-shaped paint flow adjustment component, and supplying the above-mentioned paint to the pen tip by clamping the paint flow adjustment component; a large number of disc bodies are arranged in parallel with comb-groove-shaped intervals, and are provided with slit-shaped paint guide grooves that pass through the above-mentioned disc bodies vertically in the axial direction and ventilation grooves with a width greater than the grooves, and the above-mentioned paint is guided to the pen tip through the pen core, and the pen core is provided with a paint guide core at the axis center for guiding the paint from the paint storage part to the pen tip; a mechanism having a paint flow adjustment component using a valve mechanism, and supplying the above-mentioned paint to the pen tip; a mechanism using a paint storage body or shaft cylinder with a pen tip to directly supply the above-mentioned paint to the pen tip, etc.
[0181] In one embodiment, the pen-type applicator is a marking pen such as a marker pen for coating a model assembly kit. The pen tip is not particularly limited and can be, for example, a fiber pen tip, a felt pen tip or a plastic pen tip. In addition, its shape can be bullet-shaped, chisel-shaped, brush-shaped, etc.
[0182] In one embodiment, the pen-type applicator has in a cylindrical shaft: a paint container; an agitator, which is built into the paint container and is used to stir the above-mentioned paint; and a valve mechanism, which supplies the above-mentioned paint stored in the paint container to the pen tip for adjustment, which can be a liquid-type pen body that releases the valve mechanism by pressing the pen tip and allows the above-mentioned paint to flow out to the pen tip.
[0183] When the above-mentioned paint is applied by a brush, the thickness of the film formed on the coated surface varies depending on the position where it is formed, but the properties of the obtained film are the same as those obtained by implementing other coating methods. The reason for this is not clear, but it is believed that the unevenness is formed due to the presence of an appropriate amount of pigment components.
[0184] The coating object, i.e., the object to be coated, is not particularly limited, as long as it is an object with a hard surface made of glass, resin, metal, ceramic, wood, etc. The shape of the object to be coated is also not particularly limited, and can include a plate, a (hollow) cylinder, a film, etc.
[0185] Examples of the coating include the following:
[0186] ·Electronic and electronic equipment: mobile phones, smartphones, tablet computers, personal computers, personal computer peripherals (keyboards, printers, external disks, etc.), watches, audio equipment, and various office automation equipment, etc.
[0187] Household appliances: refrigerators, vacuum cleaners, microwave ovens, televisions, video equipment, etc.
[0188] Stairs, floors, tables, chairs, cabinets, other furniture, wood products.
[0189] Various building materials, wooden floors, interior and exterior walls of buildings, etc.
[0190] Automobiles, motorcycles and other vehicles or their parts: specifically, body, interior parts (dashboard, instrument panel, handles, etc.), bumpers, spoilers, door handles, headlights, taillights, aluminum wheels, motorcycle fuel tanks, etc.
[0191] Optical applications, such as lenses assembled on various camera units, inner walls of lens barrels, inner and outer covers of lens units, lens gaskets and other camera parts.
[0192] · Glasses, goggles and similar products.
[0193] · Products of interest made of resin molded products, and their assembly parts, such as assembled models (plastic models, etc.), parts of assembled models in the model kit, etc.
[0194] <Membrane Characteristics>
[0195] The properties of the film formed from the above-mentioned coating material are as follows.
[0196] (gloss, reflectivity, L value, optical density, adhesion)
[0197] The film formed by the above-mentioned coating material preferably has a glossiness of less than 1.0%, a reflectivity of less than 1.5%, and an L value of less than 15 on the film surface. When the film formed by the above-mentioned coating material needs to have light-shielding properties during transmission, in addition to the above-mentioned characteristics (i.e., the glossiness of the film surface is less than 1.0%, the reflectivity is less than 1.5%, and the L value is less than 15), it is further preferred that the optical density of the film surface is 2.0 or more.
[0198] Here, if the film formed by the above-mentioned coating is exposed on the outermost surface, as described in the text, the glossiness, reflectivity, L value, and optical density of the film surface are preferably within the above-mentioned ranges. If the film formed by the above-mentioned coating is covered with other films, the glossiness, reflectivity, L value, and optical density of the surface of the other films, that is, the outermost surface of the film formed on the coated object, should preferably be within the above-mentioned ranges. Hereinafter, these surfaces are collectively referred to as "the outermost surface of the film".
[0199] The film formed by the above-mentioned coating material preferably has a glossiness of less than 1.0%, a reflectivity of less than 1.5%, and an L value of less than 15 on the outermost surface of the film. When the film formed by the above-mentioned coating material needs to have light-shielding properties during transmission, in addition to the above-mentioned characteristics (glossiness of the outermost surface of the film is less than 1.0%, reflectivity is less than 1.5%, and L value is less than 15), it is further preferred that the optical density of the outermost surface is greater than 2.0. By making the glossiness, reflectivity, and L value of the outermost surface of the film within the above-mentioned range according to the required optical density, low gloss, low reflectivity, high blackness, and high light-shielding properties as required on the outermost surface of the film can be achieved.
[0200] The upper limit of glossiness is more preferably less than 0.7%, and further preferably less than 0.5%. By adjusting the glossiness within the above range, flare and ghosting caused by diffuse reflection of light can be effectively prevented. The lower limit of glossiness is not particularly limited, and the lower the better.
[0201] The upper limit of the reflectivity is more preferably less than 1.25%, and further preferably less than 1.0%. The lower limit of the reflectivity is not particularly limited, and the lower the better. By adjusting the reflectivity within the above range, flare and ghosting caused by diffuse reflection of light can be more effectively prevented.
[0202] The upper limit of the L value, i.e., the blackness, is more preferably less than 12, and further preferably less than 10. The lower limit of the L value is not particularly limited, but from the perspective of seeking a darker appearance, the lower the better. By adjusting the L value within the above range, the blackness is high, the blackness is outstanding, and the design is excellent, so it can be applied to the camera unit of mobile phones such as smart phones.
[0203] The above L value refers to the lightness L* value of the outermost surface of the film in the CIE 1976 L*a*b* (CIELAB) color system by the SCE method. The so-called SCE method is a method of removing regular reflected light, that is, a method of measuring color by removing regular reflected light. The definition of the SCE method is stipulated in JIS Z 8722 (2009). Since the SCE method measures by removing regular reflected light, the color is close to the color actually seen by the human eye.
[0204] CIE is the abbreviation of Commission internationale de l'Eclairage, which refers to the International Commission on Illumination. CIELAB display color is an equal color space recommended in 1976 to measure color differences caused by differences in perception and equipment, and is specified in JIS Z 8781 (2013). The three coordinates of CIELAB are represented by L* value, a* value, and b* value. The L* value represents lightness and is expressed from 0 to 100. When the L* value is 0, it means black, and when the L* value is 100, it means diffuse white. The a* value represents the color between red and green. If the a* value is a negative value, it means that the color is close to green, and if it is a positive value, it means that the color is close to red. The b* value represents the color between yellow and blue. If the b* value is a negative value, it means that the color is close to blue, and if it is a positive value, it means that the color is close to yellow.
[0205] When the film formed by the above-mentioned coating needs to have light-shielding properties when transmitted, the lower limit of the optical density is more preferably 2.5 or more, and more preferably 3.2 or more. By adjusting the optical density within the above range, the light-shielding properties can be further improved. There is no particular restriction on the upper limit of the optical density, and the higher the better.
[0206] The above-mentioned glossiness, reflectance, L value and optical density can be measured by the following methods.
[0207] In addition to the above-mentioned properties, i.e., glossiness, reflectivity, L value, and optical density as required, the film formed by the above-mentioned coating material further preferably has good adhesion to the coating surface. The adhesion of the film formed by the above-mentioned coating material to the coating surface is shown in the adhesion evaluation in the examples described later, and preferably the residual coating film is 90% or more.
[0208] [Example]
[0209] Hereinafter, the present invention will be specifically described based on experimental examples (including examples and comparative examples), but the present invention is not limited to these experimental examples. In the following description, "part" means "part by mass" and "%" means "% by mass".
[0210] [Composition of water-based paint]
[0211] As A, that is, the resin component, the following was prepared.
[0212] A1a: acrylic resin emulsion, Mowinyl 7471 manufactured by Nippon Synthetic Chemical Industry Co., Ltd.
[0213] Acrylate copolymer, resin Tg 23℃, resin solid content 44%
[0214] A2a: Polyester resin emulsion, VYLONAL MD1200 manufactured by Toyobo Co., Ltd.
[0215] Resin Tg 67℃, resin solid content 34%, Mn 15,000, acid value 1mgKOH / g, hydroxyl value 5mgKOH / g
[0216] ·A3a: Polyvinyl alcohol, Gohsenol KH17 manufactured by Mitsubishi Chemical Corporation
[0217] Resin solid content 15%, degree of polymerization about 1700, saponification degree 78.5 to 81.5 mol%
[0218] The haze value of the film (thickness 12 μm) obtained by forming a film from a mixture of two resin solid contents (acrylic resin and polyester resin) of "Mowinyl 7471" used in A1a and "VYLONAL MD1200" used in A2a (both emulsions) at a mass ratio of 1:1 was measured using a haze meter NDH4000 manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with the method of JIS K7136. The result was 3.85% Ta. Then, the ratio of the resin solid content of A2a was changed to 1.23, 2.94, and 12.25 with respect to the resin solid content of A1a:1, and the haze value of the film after film formation was measured using the above method. The results were 4.72%, 8.55%, and 15.82%, respectively, confirming that the haze value increased with the increase in the amount of A2a mixed.
[0219] As B, that is, black material, the following was prepared.
[0220] B1a: Black acrylic beads, particle size 2 to 3 μm
[0221] RUBCOULEUR 224 (SMD) Black, manufactured by Dainichi Seika Industries, Ltd., CB content 18%
[0222] B2a: Black acrylic beads, particle size 7 to 9 μm
[0223] RUBCOULEUR 220(MD) Black, manufactured by Dainichi Seika Industries, Ltd., CB content 5%
[0224] B2b: CB, particle size 150nm
[0225] MHI Black #273, manufactured by Mikoku Color Co., Ltd., CB content 9.5%)
[0226] B2c: composite silica, particle size 3μm
[0227] BECSIA ID, manufactured by Fuji Silicon Chemical Co., Ltd.
[0228] In addition, "RUBCOULEUR 224 (SMD) Black" used in B1a and "RUBCOULEUR 220 (MD) Black" used in B2a are both true spherical acrylic resin particles containing CB, and are one of the compositions of CB and acrylic resin. "MHI Black #273" used in B2b (CB) is a CB dispersion, in which 9.5% of the total solid content of 18% is CB and the remaining 8.5% is other compounds. Among the 8.5% of other compounds, 3% are copper compounds and 5.5% are acrylic resins. "BECSIA ID" used in B2c, i.e. composite silica, is a composite particle of CB and silica, satisfying CB / silica = about 25 / 75 (mass ratio).
[0229] As C, i.e., a dilution solvent, the following was prepared.
[0230] C1: Water
[0231] C2: Alcohol
[0232] [Object to be painted]
[0233] A smartphone casing (plastic outer case) was prepared as an object to be coated.
[0234] [Experimental Examples 1 to 23, 4a to 17a]
[0235] 1. Preparation of water-based coatings
[0236] The components of each experimental example were added to a mixed solvent of water and alcohol in a specified amount as shown in Tables 1 and 2, so that the total solid content (mass %) and the solid content ratio of each component became the values listed in Tables 1 to 3, and a water-based paint was prepared by stirring and mixing, which will also be referred to as "paint" hereinafter.
[0237] 2-1. Formation of membrane 1
[0238] The coating obtained in each experimental example was sprayed onto the object to be coated by the same spraying method as described in the following (3-3-1) Coating Property 1 to form a coating film, and then the coating film was allowed to stand at room temperature for about 5 to 10 minutes to form a film 1 formed by the spraying method with an average thickness of 20 μm on the coated surface of the object to be coated.
[0239] 2-2. Formation of Film 2
[0240] The object to be coated was also fully coated using the marker pen used in the following (3-3-2) Coating Property 2 to form a coating film, which was then left to stand at room temperature for about 5 to 10 minutes to form a film 2 formed by writing with an average thickness of 10 μm on the coated surface of the object to be coated.
[0241] 3. Evaluation
[0242] The various properties (viscosity, injectability, coating properties 1 and 2, dripping properties) of the coatings obtained in each experimental example were evaluated using the methods shown below, that is, coating evaluation was performed. In addition, the various properties of the films 1 and 2 formed by the coatings obtained in each experimental example were evaluated by the methods shown below, that is, film evaluation was performed. The results are shown in Tables 1 to 3.
[0243] [Paint Evaluation]
[0244] (3-1-1) Viscosity 1
[0245] The viscosity 1 of the coating material was measured using a B-type viscometer VISCOMETER BM2 manufactured by Toki Sangyo Co., Ltd. under the conditions of 25° C., 60 rpm, 1 minute, and rotor No. 1. The evaluation criteria are as follows.
[0246] ○: Viscosity is 1 mPa·s or more and 50 mPa·s or less, and the viscosity is good
[0247] ×: Viscosity exceeds 50 mPa·s, which is too high
[0248] (3-1-2) Viscosity 2
[0249] The viscosity 2 of the coating material was measured using a B-type viscometer VISCOMETER BM2 manufactured by Toki Sangyo Co., Ltd. at 25° C., 60 rpm, 1 minute, and rotor No. 2. The evaluation criteria were as follows.
[0250] ○: Viscosity is 80 mPa·s or more and 230 mPa·s or less, and the viscosity is good
[0251] ×: Viscosity exceeds 230 mPa·s, which is too high
[0252] (3-2) Injectability
[0253] The injectability of the paint was evaluated by observing the injection of the paint into the air atomizer.
[0254] Using an air sprayer in which an air brush, Spraywork HG Single Air Brush, manufactured by TAMIYA Co., Ltd., was attached to Spraywork AirCan 420D, manufactured by TAMIYA Co., Ltd., the injectability of each paint was evaluated by visually observing the flow of the paint from the air brush cup into the nozzle. The evaluation criteria are as follows.
[0255] ○: There is no clogging at all, and the liquid enters the nozzle smoothly.
[0256] △: There is no clogging, but the speed at which the liquid enters the nozzle is slightly slow.
[0257] ×: The liquid is clogged and does not enter the nozzle.
[0258] (3-3-1) Coating properties 1
[0259] The coating properties of the coatings were evaluated by observing the coating unevenness after spraying. Each coating was injected into the air atomizer used in (3-2) above, sprayed from 10 cm from the front end of the air brush toward the outer surface of the object to be coated for 10 seconds, and then the coating unevenness of the formed coating film before drying was visually evaluated.
[0260] (3-3-2) Coating properties 2
[0261] The coating properties of the coating were evaluated by observing the coating unevenness after writing with a marker pen. The coating obtained in each experimental example and a stainless steel ball with a diameter of 5 mm for stirring were simultaneously filled into the cylindrical barrel of the liquid pen body uni POSCA PC-1M manufactured by Mitsubishi Pencil Co., Ltd. by pressing the pen tip to release the valve, and then assembled to prepare a marker pen including a chisel-shaped polished pen tip. Using this marker pen, a 2 cm square area on the object to be coated was painted from the vertical direction, and the coating unevenness of the formed coating film before drying was visually evaluated.
[0262] The evaluation criteria of coating properties 1 and coating properties 2 are as follows.
[0263] ⊚: No coating unevenness, that is, no thickness unevenness was observed.
[0264] ○: Slightly uneven coating was observed.
[0265] ×: Uneven coating was observed over a wide range.
[0266] (3-4) Drip
[0267] The dripping property of the paint is evaluated by observing the dripping of the paint from the coated object after spraying.
[0268] As in (3-3-1) above, each coating was injected into the air atomizer used in (3-2) above, and sprayed on the outer surface of the object to be coated from a distance of 10 cm from the front end of the air brush for 10 seconds, and the dripping of the attached droplets from the object to be coated was evaluated. The evaluation criteria are as follows.
[0269] ○: After coating, no dripping occurs even when the coated object is placed vertically.
[0270] △: When the coated object is placed vertically after coating, the liquid gradually drips.
[0271] ×: When the coated object is placed vertically after coating, the liquid drips immediately.
[0272] [Membrane evaluation]
[0273] (3-5) Characteristics
[0274] -Glossiness-
[0275] The glossiness of the surfaces of the films 1 and 2 formed on the respective coated objects with respect to the measured light at an incident angle of 60°, i.e., the 60° specular glossiness, was measured at 9 points using a gloss meter VG 7000 manufactured by Nippon Denshoku Industries Co., Ltd. according to the method shown in JIS Z8741, and the average value was taken as the glossiness. The evaluation criteria are as follows.
[0276] ◎: Glossiness is less than 0.5%, excellent low glossiness
[0277] ○: Glossiness is 0.5% or more and less than 0.7%, excellent in low glossiness
[0278] △: Glossiness is 0.7% or more and less than 1.0%, and low glossiness is good
[0279] ×: Glossiness is 1.0% or more, and low glossiness is insufficient
[0280] -Reflectivity-
[0281] The reflectance of the surface of the films 1 and 2 formed on each coated object with respect to light of a wavelength of 550 nm, i.e., the 550 nm reflectance, was measured at 9 points using a spectrophotometer CM-5 manufactured by Konica Minolta according to the method shown in JIS Z8722, and the average value was taken as the reflectance. The evaluation criteria are as follows.
[0282] ◎: Reflectivity is less than 1.0, and low reflectivity is extremely excellent
[0283] ○: Reflectivity is 1.0% or more and less than 1.25%, excellent in low reflectivity
[0284] △: Reflectivity is 1.25% or more and less than 1.5%, good low reflectivity
[0285] ×: Reflectivity is 1.5% or more, low reflectivity is insufficient
[0286] -Blackness-
[0287] The blackness of the surfaces of the films 1 and 2 formed on the respective coated objects was evaluated by measuring the lightness L* value of the CIE1976L*a*b* (CIELAB) color system of the film surfaces by the SCE method. The lightness L* value was measured using a spectrophotometer CM-5 manufactured by Konica Minolta in accordance with the method of JIS Z8781-4:2013. The evaluation criteria are as follows.
[0288] In the measurement, CIE standard illuminant D65 was used as the light source, the viewing angle was 10°, and the L* value in the CIELAB color system was calculated using the SCE method. CIE standard illuminant D65 is specified in JIS Z 8720 (2000) "Illuminate (standard light) and standard light source for color measurement", and the same is also specified in ISO 10526 (2007). CIE standard illuminant D65 is used to represent the color of objects illuminated by daylight. Regarding the viewing angle of 10°, it is specified in JIS Z 8723 (2009) "Visual comparison method of surface color", and the same is also specified in ISO / DIS 3668.
[0289] ◎: L value is less than 10, and the blackness is excellent
[0290] ○: L value is 10 or more and less than 12, and the blackness is excellent
[0291] △: L value is 12 or more and less than 15, and the blackness is good
[0292] ×: L value is 15 or more, and blackness is insufficient
[0293] -Light blocking properties-
[0294] The light-shielding property of the films 1 and 2 formed on each coated object is evaluated by calculating the optical density of the coating film. The optical density of the films 1 and 2 formed on each coated object is calculated by using a densitometer X-rite 361T (Ortho filter) manufactured by Japan Flat Panel Machinery Co., Ltd., by irradiating a vertically transmitted light beam to the film side of the coated object, and expressing the ratio to the film-free state in log (logarithm). An optical density of 6.0 or above is the upper detection limit of the measurement. The evaluation criteria are as follows. In addition, this evaluation assumes that the coated object itself has transmittance, and the film formed thereon is required to have light-shielding properties. If the film is not required to have light-shielding properties, the evaluation here will not affect the comprehensive evaluation.
[0295] ◎: Optical density is 3.2 or above, and light shielding is excellent
[0296] ○: Optical density is 2.5 or more and less than 3.0, and light shielding property is excellent
[0297] △: Optical density is 2.0 or more and less than 2.5, and light shielding is good
[0298] ×: Optical density is less than 2.0, light shielding property is insufficient
[0299] - Adhesion -
[0300] The adhesion of the films 1 and 2 formed on each of the coated objects to the surface of the coated object was evaluated by cutting the film in a checkerboard pattern with a commercially available utility knife, sticking a transparent tape Cellotape manufactured by NICHIBAN on it, and then tearing it off, and visually confirming the remaining state of the film. The evaluation criteria are as follows.
[0301] ◎: 100% residual film, excellent adhesion
[0302] ○: Residual film is 95% or more and less than 100%, and the adhesion is excellent
[0303] △: Residual film is more than 90% and less than 95%, and the adhesion is good
[0304] ×: The remaining film is less than 90%, and the adhesion is insufficient
[0305] - Comprehensive Assessment -
[0306] The above-mentioned glossiness, reflectivity, blackness and adhesion were comprehensively evaluated. The evaluation criteria are as follows. As for light shielding, as mentioned above, it may be necessary or not, so it was excluded from the comprehensive evaluation.
[0307] ◎: Glossiness, reflectivity, blackness, and adhesion were all ◎
[0308] ○: At least one of the evaluations of glossiness, reflectivity, blackness, and adhesion was ○, and none of them was ×.
[0309] ×: At least one of each of the evaluations of glossiness, reflectivity, blackness, and adhesiveness was ×.
[0310] [Table 1]
[0311]
[0312] [Table 2]
[0313]
[0314] [Table 3]
[0315]
[0316] 4. Test
[0317] As shown in Table 1, when the composition contained in the coating does not contain at least one of (A1) and (A2) as (A) (Experimental Examples 1 to 3), at least one of the film characteristics of glossiness, reflectivity, L value, and adhesion cannot be satisfied. On the other hand, even if the composition contains both (A1) and (A2) as (A) (Experimental Examples 4 to 10), if the mass ratio of the resin solid content of (A2) to the resin solid content of (A1): 1 is less than 1.8 (Experimental Example 4) or greater than 4.4 (Experimental Example 10), the film characteristic of adhesion cannot be satisfied. Even if both (A1) and (A2) are contained, and the mass ratio of the resin solid content of (A2) relative to the resin solid content of (A1) is in an appropriate range of 1.8 to 4.4 (Experimental Examples 6 and 11 to 17), if (B) does not contain (B1) with a particle size within the specified range (Experimental Examples 11 to 13), or (B) contains (B1) with a particle size within the specified range, but the mass ratio of (B) relative to the resin solid content of (A1) is less than 1.3 (Experimental Example 14), or greater than 4.0 (Experimental Example 17), at least one of the film properties of gloss, reflectivity, L value, and adhesion cannot be satisfied.
[0318] In contrast, if the mass ratio of the resin solid content of (A1) to 1:1, the resin solid content of (A2) is in an appropriate range, i.e., greater than 1.8 and less than 4.4, and if the mass ratio of the resin solid content of (A1) to 1:1, the resin solid content of (B) is also appropriate, i.e., greater than 1.3 and less than 4.0 (such as Experimental Examples 5 to 9, 15, and 16), all the characteristics of the coating and the film can be met.
[0319] As shown in Table 2, even if the composition contained in the coating contains both (A1) and (A2) as (A) (Experimental Examples 4a to 10a), if the mass ratio of the resin solid content of (A2) relative to the resin solid content of (A1) is less than 1.8 (Experimental Example 4a) or greater than 4.4 (Experimental Example 10a), the adhesion of the film characteristics cannot be satisfied. Even if both (A1) and (A2) are contained, and the mass ratio of the resin solid content of (A2) relative to the resin solid content of (A1) is in an appropriate range of 1.8 to 4.4 (Experimental Examples 6a and 11a to 17a), if (B) does not contain (B1) with a particle size within the specified range (Experimental Examples 11a to 13a), or (B) contains (B1) with a particle size within the specified range, but the mass ratio of (B) relative to the resin solid content of (A1) is less than 1.3 (Experimental Example 14a), or greater than 4.0 (Experimental Example 17a), one or more of the film properties of gloss, reflectivity, L value, and adhesion cannot be satisfied.
[0320] In contrast, if the mass ratio range of the resin solid content of (A2) relative to the resin solid content of (A1) is appropriate, i.e., greater than 1.8 and less than 4.4, and if the mass ratio of (B) relative to the resin solid content of (A1) is also appropriate, i.e., greater than 1.3 and less than 4.0 (Experimental Examples 5a to 9a, 15a, 16a), all the characteristics of the coating and the film can be met.
[0321] As shown in Table 3, when the amounts of (B) and (A) are fixed and the ratio of (A1) to (A2) in (A) varies (Experimental Examples 6 and 18 to 23), as the ratio of the resin solid content of (A2) relative to the resin solid content of (A1) increases, the glossiness and reflectivity of the model characteristics can be maintained at a high level, while the L value and the optional light shielding property can be improved. In addition, the haze value in Table 3 is the haze value of a film having a thickness of 12 μm obtained by forming a mixture not containing (B), wherein (A1a) and (A2a) are mixed according to the mass ratio (converted to the resin solid content) shown in Table 3. As described above, the values measured using a haze meter NDH4000 manufactured by Nippon Denshoku Industries Co., Ltd. according to JIS K7136.
[0322] [Experimental Example 24]
[0323] A water-based paint was prepared, the composition of which was the same as that in Experimental Example 6, except that black acrylic beads having a slightly larger particle size, i.e., a particle size of 5 to 6 μm, were used instead of B1a as the black pigment. The black acrylic beads were true spherical acrylic resin particles containing CB like B1a. Then, films 1 and 2 were formed by the same method as above, and the same evaluation was performed, and the same evaluation as that of Experimental Example 6 was obtained.
Claims
1. A composition, which is a water-based resin composition for coating, It contains at least (A) and (B), (A) a mixture containing a plurality of mutually incompatible water-dispersible resins, wherein as one of the water-dispersible resins in the mixture, a water-dispersible resin is used, the haze value of a film formed by the mixture with one or more other water-dispersible resins increases as the mixing amount increases, (B) contains 90% by mass or more of (B1) having a particle size of 2 μm or more and 4 μm or less, and the mass ratio of (B) to the resin solid content of (A):1 is 1.3 or more and 4.0 or less, in, (A) is a film-forming resin component, (B) is black material, (B1) is a composite of a black pigment and a resin.
2. A composition, which is a water-based resin composition for coating, It contains at least (A) and (B), (A) contains 90% by mass or more of (A1) and (A2), and the mass ratio of the resin solid content of (A2) to the resin solid content of (A1):1 is 1.8 to 4.4, (B) contains 90% by mass or more of (B1) having a particle size of 2 μm or more and 4 μm or less, and the mass ratio of (B) to the resin solid content of (A):1 is 1.3 or more and 4.0 or less, in, (A) is a film-forming resin component, (A1) is an acrylic resin emulsion, (A2) is a polyester resin emulsion, (B) is black material, (B1) is a composite of a black pigment and a resin.
3. The composition according to claim 1 or 2, wherein (B1) Contains acrylic resin particles containing carbon black.
4. The composition according to claim 2 or 3, (A) further contains (A3), and the mass ratio of (A3) to the resin solid content of (A1):1 is 1.2 to 1.7, in, (A3) is a water-soluble polymer.
5. A coating material comprising the composition according to any one of claims 1 to 4, and (C), wherein the viscosity measured at 25°C by a B-type viscometer is 1 mPa·s or more and 300 mPa·s or less, in, (C) is a diluting solvent.
6. The coating material according to claim 5, which is used for coating model parts.
7. The coating material of claim 5, which is used for coating camera parts. 8 . The coating material according to claim 5 , which is used for coating by a spray coating method, and has a viscosity of 1 mPa·s to 50 mPa·s as measured at 25° C. using a B-type viscometer.
9. A pen-type applicator, the interior of which is filled with the coating material according to claim 5, and the viscosity of the pen-type applicator measured at 25°C by a B-type viscometer is 80 mPa·s or more and 230 mPa·s or less.
10. A film formed from the coating material according to claim 5, wherein: The glossiness of the outermost surface of the film-formed surface for incident light at an incident angle of 60° is less than 1.0%, the reflectivity for light of a wavelength of 550 nm is less than 1.5%, and the L value in the CIELAB colorimetric system measured by SCE is less than 15.
11. The film of claim 10, wherein When the film needs to have light-shielding properties when transmitted, the optical density of the outermost surface of the film-forming surface is 2.0 or more.
Citation Information
Patent Citations
Portable unit and decorative film
JP2007285093A
Photo-curable resin composition exhibiting light-blocking properties and tackiness, and cured product thereof
CN102227475A
Carbon black for waterborne coatings
CN105555884A